ELDERLY SELF ADJUSTMENT AT TRESNA WERDHA BLITAR SOCIAL SERVICES TULUNGAGUNG DORMITORY - Almera Nestyan Faemy; Rini Hartini Rinda Andayani; Sri Ratna Ningrum (Indonesian Journal of Social Work, 2021)
This research is motivated by the living conditions of the elderly who must feel living in social service institutions or orphanages. Being separated from family, limited family care and neglect are some of the reasons why the elderly live in orphanages. The elderly who are in the orphanage are required to be able to adapt, both to various rules, to the physical and social environment. This study aims to describe the characteristics of the elderly, personal adjustment, social adjustment and the barriers of the elderly in adjustment. This study uses a qualitative approach with a descriptive method. Data collection techniques through in-depth interviews, participatory observation and documentation studies. Purposive sampling technique to determine six informants, consisting of the elderly and nursing home staff. Examination of the validity of the data and data analysis techniques using qualitative tests. The results of the study indicate that there are still elderly informants who have problems in personal adjustment, namely there are elderly who have not been able to accept their physical conditions and illness conditions, so they experience emotional shocks such as complaining and feeling disappointed in themselves. While in social adjustment, there are elderly who experience problems in interacting, have disharmonious relationships, and obstacles in interacting with nursing home staff due to distrust of nursing home staff. The conclusion of the research is that the adjustment of the elderly requires social support from professional caregivers, especially because the elderly who are in the orphanage are rarely visited by their families. The main recommendation is the need for caregivers who understand the needs of the elderly, it is also necessary to develop individual and group therapies that will help the elderly to be able to enjoy their old age well in the orphanage.